Pancasila Sebagai Sumber Nilai Pembentukan Peraturan Perundang-Undangan - Rafi Akbar Wirawansyah; Zainal Arifin Hoesein (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Pancasila, aspthe foundation ofpthe Indonesianpstate, serves as thepultimate source ofpall sources ofplaw in the country. Although often a topic of daily discussion, Pancasila does notpseem to be explicitly mentioned in the Indonesian constitution. Therefore, this article aims to examine thepposition of Pancasila aspthe foundation of allpsources ofplaw, as well as formulatepsteps forpits application in buildingptheprule ofplaw in Indonesia. Thepresearch method appliedpin this article ispa literaturepstudy approach, usingpdata and referencespfrom various sources suchpas scientific journals,pe-books,particles, and relevantpmagazines. The purpose ofpthis writing ispto explorepmore deeply the conceptpof Pancasila aspthe basispof the entire framework of legislation in the Indonesian legal state, explain how Pancasilapis applied aspthe mainpsource ofplaw in the process of forming apstate ofplaw inpIndonesia, so that it can be understood the positionpof Pancasila aspthe foundation ofpall laws andpregulations, andphow it is applied as the main source ofplaw.